Iowa Birdline update, March 25, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for March 25, 1991. Highlights include early Eastern Phoebes, a Varied Thrush, a Cinnamon Teal and continued waterfowl migration. Epson - sheet feed/flatbed